Vitamin D Levels in Different Severity Groups of Schizophrenia - Akinlade, Kehinde Sola; Olaniyan, Oyejide Afolabi; Lasebikan, Victor Olufolahan; Rahamon, Sheu Kadiri (Frontiers in Psychiatry, 2017)
Background: Vitamin D deficiency (VDD) continues to be associated with schizophrenia, but there is the dearth of information on the relationship between the severity of schizophrenia and plasma levels of vitamin D. This study, therefore, determined the plasma levels of vitamin D in different severity groups of schizophrenia. Materials and methods: Plasma level of vitamin D was determined in 60 patients with schizophrenia and 30 apparently healthy individuals who served as controls. Patients with schizophrenia were classified into mildly ill, moderately ill, markedly ill and severely ill groups using the Positive and Negative Syndrome Scale (PANSS). Results: The mean level of vitamin D was significantly lower in patients with schizophrenia compared with the controls. Similarly, there was a significant association between VDD and schizophrenia. The mean plasma levels of vitamin D were not significantly different when the mildly, moderately, markedly and severely ill groups were compared with one another and there was no significant correlation between vitamin D level and PANSS scores. Furthermore, patients on atypical antipsychotics had an insignificantly lower level of vitamin D compared with the patients on typical antipsychotics. Conclusion: It could be concluded from this study that patients with schizophrenia have low plasma vitamin D level which does not appear to be associated with the severity of schizophrenia and type of antipsychotics. Therefore, regular screening for vitamin D status of patients with schizophrenia is suggested in order to allow for the institution of appropriate clinical intervention when necessary.